Effect of a six-month iron-zinc fortified milk supplementation on nutritional status, physical capacity and speed learning process in Indonesian underweight schoolchildren: randomized, placebo-controlled (Medical Journal of Indonesia, 2009)
Aim to evaluated the effect of milk supplementation enriched with iron and zinc on indicators of growth, physical capacity and cognitive performance in underweight school-children. Method Two-armed, randomized controlled double-blind trial was performed in several primary schools in Jakarta and Surakarta, Indonesia. A total of 245 underweight schoolchildren aged 7-9 years living in urban poor areas of Jakarta and Solo were randomly allocated to receive two cups of iron-zinc fortified-milk (n = 121) or non-iron-zinc fortified milk (n= 124) supplementation daily for six months. Biochemical indicators, anthropometric indices, physical capacity and cognitive performance were measured at before and after the supplementation. Results The study shows that between the fortified and non-fortified milk group, there was no significant different in haemoglobin increase (0.01 + 0.96 mg/dL versus 0.17 + 0.81 mg/dL) nor serum ferritin increase (12.77 + 25.50 mcg/dL versus 14.99 + 29.56 mcg/dL). Unexpectedly, decreased in serum zinc was found in both groups (3.01 + 3.24 mMol/dL and 3.12 + 3.71 mMol/dL). There was significant higher increment (P=0.045) in body weight among the fortified milk group (1.31 + 0.69 kg) as compared to the non-fortified group (1.13 + 0.69 kg). Consistently, there was significant increase (P=0.025) in the indicator of underweight (WAZ) among the fortified milk group (1.47 + 0.50) as compared to the non-fortified group (1.33 + 0.47). There was significant improvement (P=0.001) of cognitive performance, i.e. coding test-score among the fortified group (12.74 + 11.76) as compared to the non-fortified group (8.31 + 9.60), but there was no significant difference found in the improvement of physical capacity score in both groups (10323.77 + 9253.83 versus 8435.94 + 8824.55). Conclusion Among underweight schoolchildren aged 7-9 y, supplementation of milk fortified with iron and zinc can provide better growth, and better speed processing of learning ability. (Med J Indones 2009; 18: 193-202)